2019
DOI: 10.1002/cbm.2123
|View full text |Cite
|
Sign up to set email alerts
|

The Violence Reduction Programme: An exploration of posttreatment risk reduction in a specialist medium‐secure unit

Abstract: BackgroundThere is limited evidence for treatment programmes for offenders with a diagnosis of personality disorder deemed to be of high risk of violence towards others.AimThis study sought to evaluate change in clinician‐rated risk of violence in males among offenders accepted to a specialist medium‐secure hospital providing treatment based on the Violence Reduction Programme (VRP).MethodA retrospective, records‐based cohort study design was used to explore change in risk of violence in a sample including fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Nine instruments had some evidence for their reliability, which focused primarily on interrater, rather than test-retest reliability. Measurement error had limited evidence with studies identified for three instruments [48][49][50]. The quality of evidence for measurement error in the review was consistently low, relying on quantitative methods alone, with no attempt to relate the statistical error to the minimal important clinical change [31].…”
Section: Quality Of Evidence For the Selected Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine instruments had some evidence for their reliability, which focused primarily on interrater, rather than test-retest reliability. Measurement error had limited evidence with studies identified for three instruments [48][49][50]. The quality of evidence for measurement error in the review was consistently low, relying on quantitative methods alone, with no attempt to relate the statistical error to the minimal important clinical change [31].…”
Section: Quality Of Evidence For the Selected Instrumentsmentioning
confidence: 99%
“…Three primary types of hypotheses were identified: prediction of future events, such as violence, self-harm, and victimization; difference between subgroups, based on characteristics such as sex, ward type or behavior; and correlation with other measures. Evidence for responsiveness was identified for seven instruments, with only two demonstrating adequate properties in this respect [48,51]. See Table 2 for an overview of the evidence for the selected instruments and Supplementary Material 5 for a detailed summary.…”
Section: Quality Of Evidence For the Selected Instrumentsmentioning
confidence: 99%
“…On the other hand, minor institutional misconduct consisted of all the other less serious infractions such as common assault on any other inmate, using indecent, violent, threatening or insulting language or defiance etc (Singapore Statues Online, 2020). Studies had suggested institutional misconduct and violent reoffending to be driven by similar underlying mechanisms (Horgan, Charteris & Ambrose, 2019). Findings had proposed that these underlying behavioral tendencies were likely to show continuity prior to incarceration, through incarceration, and even after release, highlighting the potential of violent tendencies and responses to problems to be consistent regardless of contexts (Lai, 2019).…”
Section: Similarities In Factors Predicting Violent Recidivism For Fi...mentioning
confidence: 99%